The experience of career guidance of high school students at pedagogical specialties - Khmil, Natalia; Kyselyova, Olesia; Chetaeva, L. (My University, 2019)
The article highlights the experience of conducting career guidance work with high school students of pedagogical specialties by teachers of the Department of Informatics of the Communal Institution "Kharkiv Humanitarian and Pedagogical Academy" of the Kharkiv Regional Council in the conditions of modern society
Khmil N. A. The experience of career guidance of high school students at pedagogical specialties / N. A Khmil , О. В., Куselуоvа, L. P Chetaeva // Модернізація освітньої системи: світові тенденції та національні особливості : ІІ Міжнар. наук. конф. (Каунас, Литва, 22 лютого 2019 р.). – Каунас, 2019. – С. 219–222.
Keywords: профорієнтаційна робота, педагогічні спеціальності, кафедра інформатики, інформатизація суспільства; career guidance work, pedagogical specialties, department of informatics, informatization of society